Teacher Education System as a Barrier to Changes in Education: Analysis of Teachers’ Statements - Atroszko, Bartosz (INSTED: Interdisciplinary Studies in Education & Society, 2024)
The aim of the article is to present the results of a study on the meanings given by teachers to barriers to change in education. The participants of the qualitative interviews were 15 secondary school teachers. The article focuses on the barriers to change related to the teacher education system. As research participants believe, this problem consists of (1) lack of appropriate selection for the profession, (2) excessively theoretical education detached from school practice, as a consequence of which (3) teachers lack competencies and are unprepared for work in the profession, (4) they cannot cooperate with other teachers and are lonely at school, and (5) society lacks confidence in their work.